MRI enhancement of the facial nerve with Gd-DTPA--first report--experimental study on the enhancement mechanism used in viewing vascular permeability of the facial nerve - Yanagida, M (Nippon Jibi Inkoka Gakkai Kaiho, 1993)
Although there have recently been numerous reports of enhanced MRI in patients with facial palsy, the mechanism of enhancement remains largely unknown. In the present study, animal models with experimentally induced facial paralysis were prepared, and the vascular permeabilities of normal and damaged facial nerves were assessed using Evans blue albumin (EBA) as a tracer. The Gd-DTPA contents in normal and compressively damaged facial nerves were also investigated. The following results were obtained: 1. In the normal intratemporal facial nerve, EBA remained in the vessels, and did not leak into the endoneurium. In contrast, vascular permeability was very high in the epineurium and the geniculate ganglion which showed leakage of large amounts of EBA from vessels. 2. At the site of compression in the damaged nerve, EBA leakage was also seen in the endoneurism, indicating accentuated vascular permeability. This accentuation of vascular permeability shifted toward the distal side. However, no EBA leakage was seen on the side proximal to the site of compression. 3. Significantly higher Gd-DTPA contents were obtained in the facial nerve on the paralytic side than in that on the normal side (p < 0.001). As for differences between the distal and proximal sides, the distal side had a significantly higher Gd-DTPA content (p < 0.01). Assessment of vascular permeability with EBA revealed accentuated vascular permeability on the side distal to the site of compression. These results showed the presence of a blood nerve barrier (BNB) in the facial nerve.(ABSTRACT TRUNCATED AT 250 WORDS)